Ancient Egyptian imperialism - Morris, Ellen Fowles (John Wiley & Sons, Incorporated, 2018)
Intro -- Title Page -- Copyright Page -- Contents -- Acknowledgments -- Chronology of Ancient Egypt -- Introduction -- Chapter 1 Trade Before Empire -- Empire Before the State (c. 3500-2686) -- Establish Unmitigated Access to Highly Valued Resources -- Lower Nubia and the Early State -- Southern Canaan and the Early State -- Disrupt the Traditional Power Structures of Enemies -- Create Allies where Enemies had Existed Before -- Crush Resistance -- Assume Direct and Indirect Control over Large Quantities of Land and Labor -- Erect an Infrastructure so that Resources may be Cultivated and Collected in an Orderly and Efficient Manner -- Conclusion -- Notes -- Chapter 2 Settler Colonialism (c. 2400-2181) -- Settler Colonialism and an Encounter Between Others -- Close Encounters Prior to Intensive Colonialism -- Motivations for Colonization -- A Safer Trade Route -- Food Security -- The Beginning of the Colony -- The Colony at its Zenith -- The End of the Colony -- Postscript -- Notes -- Chapter 3 Military Occupation (c. 2055-1773) -- Fortification -- Control Outside the Fortresses -- Rejection and Resistance -- Notes -- Chapter 4 Transculturation, Collaboration, Colonization (c. 1773-1295) -- Crumbling Barriers -- Becoming Kin -- Altering Alliances -- A New Kingdom -- A Revised Strategy -- Collaboration -- Discrepant Experiences of Empire -- Notes -- Chapter 5 Motivation, Intimidation, Enticement (c. 1550-1295) -- Plunder -- Glory -- Recognition -- Revenue -- Coercion and Enticement in Imperial Attainment -- Notes -- Chapter 6 Organization and Infrastructure (c. 1458-1295) -- Campaign regularly in order to Naturalize Rule and Assess Resources -- Underwrite the costs of Empire Locally -- Institute a System of Staple Finance -- Co-opt, Don't Construct -- Fight Canaanites with Canaanites -- Gain Leverage Over Current and Future Leaders.